2009
DOI: 10.1007/s00572-009-0277-7
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal species associated with Pinus radiata in New Zealand including novel associations determined by molecular analysis

Abstract: Ectomycorrhizal (ECM) associates of the exotic plantation species Pinus radiata were investigated above and below ground over two years in the North Island of New Zealand. ECM species were identified using morphological and molecular (restriction fragment length polymorphism and DNA sequencing) analysis. Eighteen ECM species were observed fruiting above ground; 19 ECM species were identified below ground. In the above ground study, Wilcoxina mikolae, Rhizopogon pseudoroseolus and Inocybe sindonia were noted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Most UK alien species were from elsewhere in the Northern hemisphere and therefore may be more phylogenetically ‘familiar’ to native fungi. This is supported by Bahram et al (2013) who found many native fungi on alien Pinus in Iran, compared with the prevalence of alien fungi on Pinus in the Southern Hemisphere (Nuñez et al 2009; Dickie et al 2010; Walbert et al 2010). …”
Section: Discussionmentioning
confidence: 74%
“…Most UK alien species were from elsewhere in the Northern hemisphere and therefore may be more phylogenetically ‘familiar’ to native fungi. This is supported by Bahram et al (2013) who found many native fungi on alien Pinus in Iran, compared with the prevalence of alien fungi on Pinus in the Southern Hemisphere (Nuñez et al 2009; Dickie et al 2010; Walbert et al 2010). …”
Section: Discussionmentioning
confidence: 74%
“…ECM fungi lacking some of the physiological and ecological adaptations necessary to facilitate invasion may yield slower invasions, or may coinvade only when other, complementary fungi are also present. However, Suillus species are found virtually wherever Pinus species occur, including almost all sampled regions outside the native range where pines have been introduced (, , , , Walbert et al 2010, Hynson et al 2013). commented that “99 percent of all practicing foresters will not have to lose any sleep over the problem of mycorrhizal infection.” Unfortunately, it seems likely that many invasive pines, too, will not have to lose too much sleep over absence of co invasive mycorrhizal fungi, since the presence of a few species with high dispersal ability may secure the inoculum needed for invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis by BLAST revealed 93% similarity (query coverage of 99%) with unidentified Suillus sp. K91S8 (GQ267488) from New Zealand (Walbert et al 2010) and 92% similarity (99% query coverage) with S. flavidus isolate FFP962 (JQ711908) from Canada (Jones et al 2012). The alignment of ITS sequences of selected Suillus species resulted in a data matrix comprising 28 taxa and 713 characters including gaps.…”
Section: Resultsmentioning
confidence: 99%